ON THE RECORD OF CIDARIA DISTINCTATA STAUDINGER, 1892 (LEPIDOPTERA: GEOMETRIDAE, LARENTIINAE) IN THE FERGANA VALLEY (Scientific journal of the Fergana State University, 2025)
This article presents information on the record of Cidaria distinctata (Staudinger, 1892), belonging to the subfamily Larentiinae of the family Geometridae, in the entomofauna of the Fergana Valley. The species was first described by the German entomologist Otto Staudinger in 1892 based on specimens from the Samarkand and Margilan regions. Although subsequent records of C. distinctata were reported from Turkmenistan, Tajikistan, Uzbekistan (Tashkent region), Kazakhstan, and Kyrgyzstan, no other records have been reported from the Fergana Valley since its initial detection in 1892. Research conducted in 2024 clarified the species' distribution and reconfirmed its presence in the entomofauna of the Fergana Valley. The wingspan of C. distinctata is approximately 24 mm, with yellow forewings having a dark brown basal area and a distinctive dark transverse band in the central region. Photographs of specimens collected from the vicinity of Quvasoy city, Fergana region, as well as specimens collected by Norbert Keil and co-authors from the Northern Tien Shan region of Kyrgyzstan, are provided.